(untitled) (Journal of actual problems of jurisprudence, 2023)
The article examines the issues of legislative regulation of personal subsidiary plots, including the historical aspect of development. The authors raised problematic key issues of shortcomings of the current legislation of Kazakhstan. The international experience of regulation of personal subsidiary plots has been analyzed. In the international experience of regulation, the current state and features of the development of personal subsidiary plots, private household plots are considered, as well as the structures of plots in a number of countries of the world (Germany, Canada, USA, Japan, etc.) are studied. Also, special approaches to high agricultural productivity with high results achieved in the agricultural sector of the economy due to constant economic support from governments for plots in the agricultural sector. The forms of the contract system for the development of plots are considered. The modern forms and organization of production of plots in Western Europe and the USA have been studied. The article deals with such issues as: legal status, legal regime of property of personal subsidiary regulation of relations between owners of personal subsidiary plots and various agricultural enterprises; the relationship of personal subsidiary plots with state authorities, local governments, etc. Proposals are formulated to improve the current legislation in connection with the adoption of an independent law on personal subsidiary plots. The absence of any research developments, dissertation research, scientific articles in the field of personal subsidiary plots over the past decades prompted the authors to fill this gap by contributing to the development of this area of legal science. Key words: personal subsidiary plot, food security, rights to land and property of citizens, maintenance of personal subsidiary plots.